Neuromarketing and behavior in the consumer’s buying decision in online store Asiri Munay, Lima – Peru - Valdivia Linares, Adela Francisca (2024)
This study investigates the influence of neuromarketing on consumer buying decision behavior in online stores, focusing on the emotional, instinctive and rational dimensions. The methodology used was characterized by a quantitative approach, adopting a basic non-experimental design with an explanatory level. The data was collected through a form in Google Forms, obtaining a sample of 124 potential customers of Asiri Munay store. The results revealed a strong correlation between the aforementioned dimensions and buying decision behavior in online stores, highlighting the influence of strategies that include positive emotional experiences, attractive visual stimuli and presentation of logical and persuasive information. Specifically, it was found that consumers respond favorably to strategies that generate positive emotions, visual appeal, and compelling rational arguments when making purchasing decisions in digital environments. These findings suggest the importance of integrating neuromarketing into digital marketing strategies to improve customer experience and increase online conversions. In conclusion, this study highlights the need to adapt online marketing strategies to take advantage of the emotional, instinctive and rational dimensions of buying decision behavior, which can lead to greater commercial success in the digital environment. Additionally, it provides a solid foundation for implementing neuromarketing practices in e-commerce, which can be more effective and satisfying for online businesses.